2020
DOI: 10.2196/16260
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Portal Satisfaction on Portal Use and Health-Seeking Behavior: Structural Equation Analysis

Abstract: Background Our study addresses a gap in the modern information systems (IS) use literature by investigating factors that explain patient portal satisfaction (SWP) and perceptions about health-seeking behavior (HSB). A novel feature of our study is the incorporation of actual portal use data rather than the perceptions of use intention, which prevails in the modern IS literature. Objective This study aimed to empirically validate factors that influence S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 38 publications
5
26
0
Order By: Relevance
“…First, this study addressed an important research question regarding the link between patient portal use and patient satisfaction [ 25 ]. This study diverged from earlier studies that have used few select items to measure patient satisfaction by using multiple dimensions of the HCAHPS measures for patient satisfaction ( Multimedia Appendix 3 [ 14 , 16 , 28 , 29 ]). This is a novel contribution to extant research because it helps us to discern the portal use influences on the various facets of patient satisfaction.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…First, this study addressed an important research question regarding the link between patient portal use and patient satisfaction [ 25 ]. This study diverged from earlier studies that have used few select items to measure patient satisfaction by using multiple dimensions of the HCAHPS measures for patient satisfaction ( Multimedia Appendix 3 [ 14 , 16 , 28 , 29 ]). This is a novel contribution to extant research because it helps us to discern the portal use influences on the various facets of patient satisfaction.…”
Section: Discussionmentioning
confidence: 74%
“…However, findings from review studies also confirm the inconsistency in patient satisfaction studies [ 6 ]. Although some studies have found improved patient satisfaction when electronic patient access to medical information was used [ 6 , 13 , 14 , 21 ], other studies have found mixed results [ 7 , 15 , 22 ], and a few have found that patient satisfaction data remained unchanged [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations